The ethics of transplants : why careless thought costs lives - Richards, Janet Radcliffe (Oxford : Oxford University Press, 2012)
Argues that although people have strong feelings about their own organs, the deepest problems may not lie in a simple unwillingness to make them available, but in legal and institutional restrictions on the choices they are allowed to make. Through a series of arguments the author concludes that these restrictions are not justified by our normal moral standards, and are not even a response to popular demand, but lie in deep preconceptions of the people who make the rules. Careless moral reasoning, like careless medical practice, really can cost lives.--From publisher description.
Procurement from the living -- Methodological morals -- Procurement from the dead -- Penumbral problems.
Includes bibliographical references : 268-274 and index.
Keywords: Transplantation of organs, tissues, etc. -- Moral and ethical aspects; Procurement of organs, tissues, etc -- Moral and ethical aspects